Evaluación del cultivo de eneldo en invernadero en San Pedro, Buenos Aires - Paunero, Ignacio Eugenio (Asociación Argentina de Horticultura (ASAHo), 2021)
Dill (Anethum graveolens L.) is used as a condiment in food and has medicinal properties. The objective was to determine guidelines for the management of this greenhouse crop for its fresh cut. The crop was installed in an unheated greenhouse, located in EEA San Pedro. Two container sowing dates were carried out (April 24 and May 13), using two sizes of containers (54 cm3 and 25 cm3), and two direct sowing dates in the field (June 4 and 25). Transplant was carried out when the seedlings had three true leaves. The distance between rows was 15 cm and 20 cm between hits. At harvest, the height and number of leaves per plant, the number of plants per hit and the fresh weight were measured. The quality was determined based on a subjective scale from one to five, indicating lower to higher quality, respectively, based on the presence of stains and rots. Analysis of variance and Duncan´s test (α = 0.05) were performed. The highest yields were obtained on the first sowing date using the 54 cm3 containers with a fresh weight of 4,24 kg.m-2 and quality five. The number of leaves (9.57 to 4.10) and the height of plants (65.75 to 44.20 cm) corresponded with the bibliography. Future studies should evaluate earlier planting dates and adjust fertilization.